Luz sobre o fundo escuro: Caravaggio, São Mateus e o Anjo e Amor Vitorioso (1601-1602) - Costa, Rodrigo Henrique Araújo da (2013)
Between 1601 and 1602, the Italian painter Michelangelo Merisi, known as Caravaggio, received one of his most important orders. It was the last job to finish the series dedicated to the apostle Matthew in Contarelli Chapel in Rome, a painting called St. Matthew and the Angel. By decision of the Church, Caravaggio's version lacked decorum and had to be replaced. With a new contract, Caravaggio painted a second version of St. Matthew and the Angel, which was immediately put in its destination place. Following this event, a Marquis from the Roman nobility named Vincenzo Giustiniani, who had bought the unwelcomed version of St. Matthew and the Angel, ordered Caravaggio a painting that excelled all of the paintings in the world, Love Triumphant (Amor Vincit Omnia). The reason for the change in perspective between the three paintings, the representation of subjects so diverse among themselves and the abrupt transformation of approach, aesthetic and configuration, formed the scope of this work. These three paintings by the Italian artist Michelangelo Merisi da Caravaggio (1571-1610) revealed in this dissertation a dissident and provocative artist between the sixteenth and seventeenth centuries, in a Rome recognized in historical literature for its splits and political-religious conspiracies, deeply marked by the Religious Reforms of the period. In this conjuncture, the paintings of Caravaggio made it possible to study not only the Baroque artist, but also the social relations involved, the influences of the Baroque, the idiosyncrasies of Caravaggio, the Artistic Culture, expanding what we understand as History of Paintings and covering concepts pertinent to objectives and methodology adopted, as evidence-based analysis (Clue Paradigm), Memory, Imaginary and the allegorical and pictorial representations. Notably, in the production of historical consciousness of work, we permeate our writing with printed sources from the seventeenth century and the fundamental and specific works on Caravaggio and Art History. Through the performance of the object of study we came to conclusions on Modern History, Tridentine Rome, Catholic cosmogony, the body, religious beliefs, paganism, sacred and profane, signs and clues that reveal the clash between the artist's vision and the vision of Church and society.